Mapping sleep disturbance and nap desire to dimensions of psychopathology in U.S. adults - Amelia M. Stanton; Devisi A. Ashar; Martin Seehuus (Frontiers in Psychology, 2026)
Study objectives Insomnia and nap desire are linked to heightened psychopathology, yet less is known about their associations with broad psychopathology dimensions. Wright and colleagues recently developed brief transdiagnostic scales assessing internalizing, detachment, antagonism, disinhibition, and anankastia, but these have not been evaluated in relation to sleep. We examined cross-sectional psychopathology profiles in relation to probable insomnia and daily nap desire in U.S. adults. Methods Participants ( N = 831; analytic n = 705 after attention checks) were recruited via Prolific.com and stratified into clinical (receiving psychological/psychiatric treatment) and non-clinical groups. Measures included the PHQ-9 (depression), GAD-7 (anxiety), Sleep Condition Indicator (SCI), five-factor psychopathology scales, and nap desire/behavior. Probable insomnia was defined using the SCI clinical cut-off. Analyses tested differences in psychopathology dimensions by insomnia and nap desire. Results Participants with probable insomnia showed significantly different psychopathology profiles than those without, F (1,703) = 178.57, p < 0.001, partial η 2 = 0.20, with elevated internalizing, detachment, disinhibition, and antagonism, but not anankastia. Nap desire was associated with higher psychopathology across dimensions, though effects were smaller, F (1,703) = 36.78, p < 0.001, partial η 2 = 0.05. Conclusion Probable insomnia and daily nap desire corresponded to elevated psychopathology profiles, with stronger, more differentiated effects for insomnia. Dimensional frameworks may inform sleep-focused and transdiagnostic interventions, particularly targeting internalizing and detachment.